Analisis Alat Evaluasi Penilaian Keterampilan Menulis Pada Pembelajaran Bahasa Indonesia - Ninit Alfianika (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the writing skills evaluation instrument and describe the evaluation of the writing skills assessment instrument used by Indonesian junior high school teachers. This type of research is a qualitative research using descriptive method. The data sources used in this study were 3 Indonesian language teachers who teach in junior high schools. The instruments in this study were the researchers themselves and interview guidelines. Data collection techniques were carried out by: (1) interviewing and asking for documentation in the form of lesson plans to 3 Indonesian language teachers. (2) marking the results of interviews and the part of the lesson plan related to research data, and (3) making an inventory of these data into data analysis guidelines. The analysis stage is as follows: (1) identifying the data according to the research concept. (2) classifying data based on the theory that is the reference. (3) analyzing the data by recording words related to the research. (4) interpret the data that has been analyzed in accordance with the theory used to analyze the research, and (5) conclude the results of the data description by writing a report. So, the results of this study can be concluded as follows. (1) The assessment of writing skills used by Indonesian junior high school teachers is in the form of a test. The test used is a description test. (2) In general, the writing skills assessment instrument designed by the Indonesian junior high school teacher is quite good.